2010
DOI: 10.5194/acpd-10-4823-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric Brown Clouds in the Himalayas: first two years of continuous observations at the Nepal-Climate Observatory at Pyramid (5079 m)

Abstract: Abstract. South Asia is strongly influenced by the so-called Atmospheric Brown Cloud (ABC), a wide polluted layer extending from the Indian Ocean to the Himalayas during the winter and pre-monsoon seasons (November to April). This thick, grey-brown haze blanket substantially interacts with the incoming solar radiation, causing a cooling of the Earth's surface and a warming of the atmosphere, thus influencing the monsoon system and climate. In this area, the Himalayan region, particularly sensitive to climate c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(117 citation statements)
references
References 79 publications
(12 reference statements)
7
110
0
Order By: Relevance
“…It also receives regional air masses mainly from the south. South Asian monsoon circulations influence the weather in Nepal, which is characterized by four distinct seasons: winter (December-February), pre-monsoon (MarchMay), monsoon (June-September), and post-monsoon (October-November) seasons (Bonasoni et al, 2010). The summer monsoon season is hot, humid, and rainy, with nearly 80% of the annual precipitation of 1400 mm occurring in 4 months (Giri et al, 2006).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…It also receives regional air masses mainly from the south. South Asian monsoon circulations influence the weather in Nepal, which is characterized by four distinct seasons: winter (December-February), pre-monsoon (MarchMay), monsoon (June-September), and post-monsoon (October-November) seasons (Bonasoni et al, 2010). The summer monsoon season is hot, humid, and rainy, with nearly 80% of the annual precipitation of 1400 mm occurring in 4 months (Giri et al, 2006).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Some studies of elements and carbonaceous particle concentrations have already been carried out in this region (Tripathi et al, 2005;Bonasoni et al, 2010;Kim et al, 2015;Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…3). The Cr might be from the northern Indo-Gangetic Plain where a 3 km thick brownish layer of pollutants (or ABCs) has been detected because of operation of brick kilns, vehicle emissions, steel industry or solid waste dumping, and biomass burning (Ramanathan et al, 2007;Bonasoni et al, 2010). The air mass backward trajectories suggested that more than half of the air masses at Nam Co were transported from the northern India and Nepal during the pre-monsoon season (Fig.…”
Section: Potential Source Regionsmentioning
confidence: 99%